Antimicrobial Activity of Lemongrass and Oregano essential oil against standard antibiotic resistant Staphylococcus aureus and field isolates from chronic mastitis cow - Jae-Young Choi1; Dereje Damte; Seung-Jin Lee; Jong-Choon Kim; Seung-Chun Park (International Journal of Phytomedicine, 2012)
The study was carried out to investigate the antibacterial activity of lemongrass and Oregano essential oil against standard antibiotic resistant Staphylococcus aureus strains and field isolates from a chronic mastitic cow. Disc diffusion and minimum inhibitory concentration (MIC) assay were used to investigate antibacterial activity of lemongrass and Oregano essential oil while their combined effect with antibiotic were assessed using a microbroth chequerboard technique. For identification of the essential oil component Gas Chromatography Coupled Mass Spectroscopy (GC/MS) analysis was performed. Disc diffusion assay revealed dose-dependent inhibition zone with lemongrass oil showing consistently larger inhibition zone than oregano oil. Lemongrass essential oils were further evaluated for its antibacterial activity in combination with antibiotic which resulted both synergistic and additive interaction. Lemongrass oil-amoxicillin combination showed synergistic interactions against all tested organism while the combination for lemongrass oilnorfloxacin showed synergistic effect for two field isolates and an additive for the remaining strains. The current study indicated that both lemongrass and oregano essential oils exhibit antibacterial activity, and lemongrass oil in combination with antibiotics could be a potential agent for antibacterial treatments against antibiotic resistant bacterial infections.